ENDS AND MEANS IN POLITICS: INTERNATIONAL LAW AS FRAMEWORK FOR POLITICAL DECISION-MAKING - Kapferer, Sibylle (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2002)
The international legal system in place since 1945 is based on two core principles: the repudiation of violence as a means of political action, and the protection of fundamental human rights and freedoms. It reflects the conviction that threats to international peace and security are best addressed collectively, through the procedures and institutions established for that purpose. The reality brought to the fore in the aftermath of September 11th, 2001 is very different. This paper argues that the military intervention in Afghanistan and other anti-terrorism measures undertaken by states have revealed a profound disregard for the principles and standards of international law. Far from constituting an effective response to current security concerns, the resort to force in a manner neither in keeping with the legal criteria for self-defense nor authorized by the UN Security Council, coupled with excessive restrictions of human rights, poses a threat to the very essence of the present international legal order. The paper makes a case for international law as basis for the conduct of international relations and framework for political decision-making, arguing that it is in the interest of all that those involved in political processes accept and implement its standards and principles. The paper specifically addresses the way in which international law applies to states’ efforts to respond to crimes such as those of September 11th and emphasizes the need to strengthen the rule of law not only as a sine qua non for any effective anti-terrorism strategy, but also as a matter of national self-interest.